P387 Depression in biologic-treated patients with inflammatory bowel disease during the COVID19 pandemic. (27th May 2021) - Lin, S; Bewshea, C; Chanchlani, N; Chee, D; Pollok, R C; Kennedy, N A; Ahmad, T; Goodhand, J R
Abstract: Background: Given the existential threat from COVID-19 and the consequent restrictive public health measures it is perhaps unsurprising that SARS-CoV-2 infection has been linked to increases in rates of depression in the general population. Few studies, however have addressed anxiety and depression in patients with inflammatory bowel disease (IBD) during the COVID19 pandemic. We aimed to define, in patients with IBD treated with infliximab or vedolizumab and/or an immunomodulator, the prevalence, demographic and disease-related factors associated with depression and the effect of restrictive public health measures on rates of depression. Methods: CLARITY IBD is a United Kingdom (UK) wide, multicentre, prospective observational cohort study investigating the impact of infliximab and vedolizumab and/or concomitant immunomodulators (thiopurines or methotrexate) on SARS-CoV-2 acquisition, illness, and immunity in patients with IBD. Patients were recruited between 22nd September and 23rd December 2020 and then assessed every 8 weeks. We measured depression using the 8-item Patient Health Questionnaire (PHQ-8). Secondary outcomes were anxiety and IBD-related quality of life assessed using the General Anxiety Disorder Assessment (GAD-7) and IBD-Control questionnaires, respectively. Multivariable logistic regression models were used to identify factors independently associated with depression at entry to the study. Baseline and paired responses during the third UK government's stay-at-home lockdown order which commenced on the 4th January 2021 were compared using the Wilcoxon signed-rank test. Results: The prevalence of depression at entry to the CLARITY study was 26% (1794/6933): 14% patients satisfied criteria for mild, 6% moderate and 5% severe depression. Depression scores were associated with anxiety (Spearman's rho= 0.78, p<0.0001) and poorer IBD-Control-8 quality of life scores (Spearman's rho=-0.67, p<0.0001). Multivariable analysis showed that vedolizumab (vs infliximab), steroid use, female sex, younger age, remaining at home, ulcerative colitis, comorbidity and higher income deprivation were associated with depression at entry to the study (Figure 1). Paired depression scores were unchanged between study entry and when assessed during the lockdown period (p=0.91). Conclusion: Depression was negatively associated with infliximab therapy and was unchanged during the third UK stay-at-home lockdown. Longitudinal follow up in this cohort will allow us to determine whether COVID-19 vaccination influences depression and whether depression is linked to vaccine hesitancy or impaired serological responses to SARS-CoV-2 vaccination.